Anticoagulation therapy among patients presenting to the emergency department with symptomatic atrial fibrillation – the FinFib2 study. (October 2017) - Penttilä, Tero; Mäkynen, Heikki; Hartikainen, Juha; Lauri, Timo; Lehto, Mika; Lund, Juha; Mäkijärvi, Markku; Raatikainen, Pekka
Abstract : Objectives: Atrial fibrillation (AF) causes numerous visits to emergency departments (EDs). We evaluated the thromboembolic and bleeding risk profile and use of oral anticoagulation (OAC) therapy among patients presenting with symptomatic AF to ED. Methods: Within a 2-week period, all patients whose primary reason for the ED visit was AF were enrolled into this prospective study in 35 EDs around Finland. The risk of thromboembolic and bleeding events was assessed by the CHA2 DS2 VASc and the HAS-BLED score, respectively. Thereafter, we evaluated whether OAC was used according to the contemporary management guidelines. Results: The study population included 1013 patients (mean age 70±13 years, 52.4% men) with newly or previously diagnosed symptomatic AF. The mean CHA2 DS2 VASc and HAS-BLED score was 3.1±2.1 and 1.9±1.2, respectively. At admission, 76.3% of the patients with previously diagnosed AF and CHA2 DS2 VASc score of at least 2 were using OAC (warfarin 92.3%). However, the international normalized ratio was not at the therapeutic level in 41.9% of them. At discharge, 84.1% of the high-risk patients (85.5% of previously diagnosed and 79.6% of newly diagnosed) and 57.0 and 37.0% of the moderate-risk and low-risk patients were on OAC, respectively. Of the high-risk patients, 5.4% were treated with aspirin. Conclusion: These data showed that OAC was prescribed frequently to patients with symptomatic AF and risk factors for stroke. However, in patients using warfarin, international normalized ratio was not at the therapeutic level in a large proportion of the patients with previously diagnosed AF.